Adequate versus inadequate weight gain and socioeconomic factors of pregnant women followed up in primary care - Luciane Oliveira da Silva; Mayara Ribeiro Alexandre; Ana Carolina Montenegro Cavalcante; Soraia Pinheiro Machado Arruda; Rafaella Maria Monteiro Sampaio
Abstract Objectives: to identify the socioeconomic factors associated with inadequate (excessive and insufficient) weight gain in women followed during prenatal care in Basic Health Units in a Municipality of the Countryside of Ceará. Methods: a study was carried out with 189 pregnant women. Data were tabulated in the Excel Program and data analysis was performed in the Stata Program. In the bivariate analysis, the chisquare or Fisher's exact test was used, and the Poisson multivariate regression was used for the association between variables and the excessive or insufficient weight gain. Results: insufficient weight gain was associated with the absence of the partner (RR=1.15 CI95% = 1.02 - 1.30) and excessive weight gain was associated with non-working women (RR = 0.90 CI95% = 0.84-0.96). Conclusions: absence of partner and lack of work were associated with inadequate weight gain during pregnancy.